Primary ovarian insufficiency: update on clinical and genetic findings - Federici, Silvia; Rossetti, Raffaella; Moleri, Silvia; Munari, Elisabetta V.; Frixou, Maria; Bonomi, Marco; Persani, Luca (Frontiers in Endocrinology, 2024)
Primary ovarian insufficiency (POI) is a disorder of insufficient ovarian follicle function before the age of 40 years with an estimated prevalence of 3.7% worldwide. Its relevance is emerging due to the increasing number of women desiring conception late or beyond the third decade of their lives. POI clinical presentation is extremely heterogeneous with a possible exordium as primary amenorrhea due to ovarian dysgenesis or with a secondary amenorrhea due to different congenital or acquired abnormalities. POI significantly impacts non only on the fertility prospect of the affected women but also on their general, psychological, sexual quality of life, and, furthermore, on their long-term bone, cardiovascular, and cognitive health. In several cases the underlying cause of POI remains unknown and, thus, these forms are still classified as idiopathic. However, we now know the age of menopause is an inheritable trait and POI has a strong genetic background. This is confirmed by the existence of several candidate genes, experimental and natural models. The most common genetic contributors to POI are the X chromosome-linked defects. Moreover, the variable expressivity of POI defect suggests it can be considered as a multifactorial or oligogenic defect. Here, we present an updated review on clinical findings and on the principal X-linked and autosomal genes involved in syndromic and non-syndromic forms of POI. We also provide current information on the management of the premature hypoestrogenic state as well as on fertility preservation in subjects at risk of POI.